1968
DOI: 10.1104/pp.43.12.1959
|View full text |Cite
|
Sign up to set email alerts
|

The Biogenesis of Ethylene in Penicillium Digitatum

Abstract: Abstract. The origin of the ethylene carbon skeleton in Penicilliumr digitatum appears to be intimately associated with the Krebs cycle acids, particularly the middle carbon atoms of dicarboxylic acids. Among the other compounds studied, certain carbon atoms of /-alanine, propionic acid, and methionine can be incorporated into the ethylene carbon skeleton presumablv by way of an indirect route via the Krebs cycle acids. Carbon atoms of acrylic acid, particularly C-2, were also found to be incorporated into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Sodium cis-3-chloroacrylate did not affect ethylene production. This compound has been reported to inhibit the production of labelled ethylene from [1 ~14C]acetate in Penicillium digitatum (Jacobsen and Wang 1968). More detailed studies were made with cycloheximide, sodium monofluoroacetate, HKG, and cyanide.…”
Section: (A) Screening Experimentsmentioning
confidence: 99%
“…Sodium cis-3-chloroacrylate did not affect ethylene production. This compound has been reported to inhibit the production of labelled ethylene from [1 ~14C]acetate in Penicillium digitatum (Jacobsen and Wang 1968). More detailed studies were made with cycloheximide, sodium monofluoroacetate, HKG, and cyanide.…”
Section: (A) Screening Experimentsmentioning
confidence: 99%
“…Because of its association with citrus fruits (3), ethylene production by Penicillium digitatum Sacc. has been studied extensively; cultural conditions have been defined (6, 24) and attempts made to elucidate its biosynthetic pathway (9,10,23). When the fungus is cultured on liquid media under static conditions (without shaking), ethylene production is high and appears to be related to the surface development of a mycelial mat (24).…”
Section: Introductionmentioning
confidence: 99%
“…However, in shake culture the mycelium grows as submerged ball-like structures and produces little or no ethylene although growth is equivalent or exceeds that in static culture (6,24). Ethylene produced by P. digitatum grown on liquid medium in static culture was shown (4,9,10) not to derive from methionine, the common precursor of ethylene in higher plants (11,12,25), but from 2-ketoglutarate and glutamate (4). Other, more recent studies of fungi (5,18) and bacteria (20), however, have indicated that methionine may be associated with the production of ethylene in microorganisms.…”
mentioning
confidence: 99%
“…These data suggest similarities between the ethylene-forming system in the fungus and in higher plants despite differences in precursors under some cultural conditions. The production of ethylene by Penicillium digitatum Sacc., the green mold fungus of citrus fruits, has been extensively studied (2,6,7,17). Cultural conditions affecting ethylene production were described (5,14,15), and the biosynthetic pathway partially elucidated (4,6,7).…”
mentioning
confidence: 99%